A sero – epidemiological study in a previously highly malaria endemic area in Sri Lanka - Dewasurendra, R.L.; Fernando, S. D.; Carter, R.; Karunaweera, N.D. (University of Colombo, 2010)
Kataragama lies in the dry lowland coastal plains of southeast Sri Lanka. Though this is considered as a malaria endemic area the number of malaria cases has decreased dramatically over the past 5 years